KONSEP PENDIDIK DAN PESERTA DIDIK PERSPEKTIF SYED NAQUIB AL-ATTAS - M MA'RUF (STAI Ma'had Aly Al-Hikam Malang, 2021)
This research analyzes the thoughts of Syed Muhammad Naquib Al-Attas about the concept of educators and students. This type of research uses literature. The results of the research show that the concept of Educator and Student for Syed Muhammad Naquib Al-Attas is that an educator is a teacher whose job is not only to transfer knowledge, but also to train the soul and character of students by having good moral character so that they can be used as role models for their students, while students are someone who studies at an educator where he not only prioritizes his knowledge but understands etiquette as a student as well as applies it in his life. The concept of educators and students Syed Muhammad Naquib Al-Attas is very relevant to be used as a reference in both formal and non-formal education environments in Indonesia today. Because the concept of Educator and Learner Syed Muhammad Naquib Al-Attas discusses the improvement of adab in the world of education to date.